The Freiburg School: Walter Eucken and Ordoliberalism - Viktor J. Vanberg (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik, 2004)
What has become known as the Freiburg School or the Ordo-liberal School was founded in the 1930s at the University of Freiburg in Germany by economist Walter Eucken (1891-1950) and two jurists, Franz Böhm (1895-1977) and Hans Großmann-Doerth (1894-1944). Freiburg University's "Fakultät für Rechts- und Staatswissenschaften" that included law as well as economics provided a conducive framework for the combination of legal and economic perspectives that is characteristic of the Freiburg School and of the Ordo-liberal tradition. As Böhm later said in retrospect, the founders of the school were united in their common concern for the question of the constitutional foundations of a free economy and society. In the first volume (Böhm 1937) of their jointly edited publication series Ordnung der Wirtschaft, the three editors included a co-authored programmatic introduction, entitled "Our Task" (Böhm, Eucken and Großmann-Doerth 1989), in which they emphasized their opposition to the, then still influential, heritage of Gustav von Schmoller's Historical School, and to the unprincipled relativism that, in their view, this heritage had brought about in German jurisprudence and political economy. By contrast, they stated as their guiding principle that the "treatment of all practical politico-legal and politico-economic questions must be keyed to the idea of the economic constitution" (ibid.: 23), a task for which, they said, the collaboration of law and economics "is clearly essential" (ibid.: 25).
Keywords: 330; Ordoliberalismus; Wirtschaftswissenschaftler; Persönlichkeiten; Wissenschaft; Deutschland; Eucken Walter; International School on Theory and Numerics for Conservation Laws 1997; Freiburg; Breisgau